Identity Development among Muslim Indonesian-American College Students: A Phenomenological Study - TAUFIK MULYADIN (Indonesian Research Journal in Education |IRJE|, 2018)
This study was conducted to understand Muslim Indonesian-American college students’ experiences of identity development from the perspectives of the reconceptualized model of multiple dimensions of identity (RMMDI) proposed by Abes, Jones, and McEwen (2007). Through purposeful sampling, six participants were selected for participation in this study. This study was qualitative in nature by using the phenomenological approach to capture the essence of how Muslim Indonesian-American college students experienced, processed, and interpreted their identity development in college. Questionnaire and interviews were utilized for data collection. The collected data were analyzed using the analysis procedures proposed by Moustakas (1994) including epoche, phenomenological reduction, imaginative variation, and the synthesis of structural/textural descriptions. The study revealed that the salience of four identity dimensions for Muslim Indonesian-American students including religion, culture, social class, and gender. These identity dimensions were found to be impacted by varied contextual factors such as family, the 9/11, peer support, and college support.